A fully biodegradable breathable bottom film for diapers

By using fully biodegradable materials and adding antibacterial ingredients in the diaper base film, the problems of non-degradable, insufficient breathability, poor water absorption and insufficient antibacterial properties of traditional diaper materials are solved, and the comprehensive improvement of environmental protection, breathability, water absorption and antibacterial properties are achieved.

CN119144134BActive Publication Date: 2025-04-04FUJIAN MANSHANHONG NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411649806.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-04
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The traditional diaper base material is non-degradable, resulting in environmental pollution, insufficient breathability affects the baby's comfort, poor water absorption performance leads to undry skin, and insufficient antibacterial performance increases the risk of infection.

Method used

Fully biodegradable materials such as polylactic acid and starch-based polymers are used to add plant staple fibers and bamboo fibers to form microporous structures to improve breathability, use biopolymer water-absorbing resin fillers to enhance water-absorbing properties, and add antibacterial ingredients such as polyvinyl alcohol, lavender essential oil, tea polyphenols and chitosan.

Benefits of technology

It has achieved a comprehensive improvement in environmental protection, breathability, water absorption and antibacterial properties, reduced environmental pollution, and improved the comfort and health of the baby's skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a fully biodegradable breathable bottom film for diapers, comprising the following weight components: 45-55 weight parts of polylactic acid, 35-45 weight parts of starch-based polymer, 10-12 weight parts of plant short fibers, 8-10 weight parts of bamboo fibers, 2-4 weight parts of photosensitizers, 5-10 weight parts of polyvinyl alcohol, 1-3 weight parts of lavender essential oil, 1-2 weight parts of tea polyphenols, 2-5 weight parts of chitosan, 0.6-1 weight parts of lubricants, 0.2-0.5 weight parts of antioxidants, 2-4 weight parts of nano calcium carbonate, 0.4-0.6 weight parts of masterbatches, and 4-7 weight parts of biopolymer water-absorbing resin fillers. The starch-based polymer enhances biodegradability and flexibility, the bamboo fiber improves water absorption, natural antibacterial properties and accelerates degradation, the photosensitizer accelerates the degradation rate of the material under light, and the use of biodegradable materials reduces pollution to the environment, meeting the requirements of sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diaper production, and in particular to a fully biodegradable breathable bottom film for diapers. Background Art

[0002] With the continuous improvement of environmental awareness and the popularization of the concept of sustainable development, the demand for fully biodegradable diapers in the market is growing. Traditional diapers are usually made of materials that are difficult to degrade, which will cause long-term pollution to the environment after use. Fully biodegradable diapers use biodegradable materials that can decompose quickly in the natural environment and reduce negative impacts on the environment. This growth in demand has prompted the research and development and improvement of the breathable bottom film technology for fully biodegradable diapers.

[0003] Environmental issues: Traditional diaper bottom films are mostly made of non-degradable materials, which will cause serious pollution to the environment after use. The fully biodegradable diaper breathable bottom film in this solution uses biodegradable materials such as polylactic acid and starch-based polymers, which can be decomposed by microorganisms in the natural environment, reducing the burden on the environment.

[0004] Breathability: The breathability of diapers is crucial to the comfort of babies. This solution adds plant short fibers, nano calcium carbonate and other ingredients to form a microporous structure, which improves the breathability of the bottom film, allowing the baby's skin to breathe and reducing the feeling of stuffiness and humidity.

[0005] Water absorption problem: Diapers need to have good water absorption to keep the baby's skin dry. The biopolymer water-absorbing resin filler in this solution can absorb a large amount of water, and the added bamboo fiber and other ingredients also have a certain water absorption, which improves the water absorption performance of the base film.

[0006] Antibacterial performance: The baby's skin is delicate and easily infected by bacteria. The solution contains antibacterial ingredients such as polyvinyl alcohol, lavender essential oil, tea polyphenols, chitosan, etc., which can effectively inhibit the growth of bacteria and protect the baby's skin health. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a fully biodegradable breathable bottom film for diapers, comprising the following components by weight: 45-55 parts by weight of polylactic acid, 35-45 parts by weight of starch-based polymer, 10-12 parts by weight of plant staple fibers, 8-10 parts by weight of bamboo fibers, 2-4 parts by weight of photosensitizer, 5-10 parts by weight of polyvinyl alcohol, 1-3 parts by weight of lavender essential oil, 1-2 parts by weight of tea polyphenols, 2-5 parts by weight of chitosan, 0.6-1 parts by weight of lubricant, 0.2-0.5 parts by weight of antioxidant, 2-4 parts by weight of nano calcium carbonate, 0.4-0.6 parts by weight of masterbatch, and 4-7 parts by weight of biopolymer water-absorbing resin filler.

[0008] Preferably, the plant short fibers are composed of hemp fibers, kapok fibers and coconut shell fibers;

[0009] The starch-based polymer is any one of starch grafted polyacrylic acid and starch grafted polyvinyl alcohol, and the starch-based polymer is preferably starch grafted polyacrylic acid;

[0010] Preferably, the biopolymer water-absorbing resin filler is composed of the following components by weight: 60-70 parts by weight of starch grafted acrylic acid, 30-40 parts by weight of polylactic acid-polyethylene glycol copolymer, 10-15 parts by weight of chitosan, 0.5-0.8 parts by weight of initiator, 0.3-0.5 parts by weight of crosslinking agent, and 0.2-0.4 parts by weight of surfactant.

[0011] Preferably, the initiator is any one of potassium persulfate, ammonium persulfate, azobisisobutyronitrile and benzoyl peroxide, and the initiator is preferably potassium persulfate;

[0012] The cross-linking agent is any one of polyethylene glycol diacrylate, trimethylolpropane triacrylate and divinylbenzene, and the cross-linking agent is preferably polyethylene glycol diacrylate;

[0013] The surfactant is any one of sodium dodecylbenzene sulfonate, Tween-80 and Span-80, and the surfactant is preferably Tween-80.

[0014] A method for preparing a fully biodegradable breathable bottom film for diapers, comprising the following preparation steps:

[0015] Step S1: placing polylactic acid, starch-based polymer, plant staple fiber, and bamboo fiber in a hot air circulation oven at 60-70° C. and drying for 4-6 hours, and taking them out after the moisture content is less than 0.5%;

[0016] Step S2: Add nano calcium carbonate into a high-speed mixer, and add silane coupling agent KH-550 at the same time, and stir at 40-50° C. for 30-45 minutes;

[0017] Step S3: adding polyvinyl alcohol to deionized water, stirring with a magnetic stirrer at 80-90° C. until the polyvinyl alcohol is completely dissolved, to prepare a polyvinyl alcohol solution with a concentration of 10-15% for standby use;

[0018] Step S4: adding chitosan to a dilute acetic acid solution with a pH value of 4-5, stirring with a magnetic stirrer at room temperature until the chitosan is completely dissolved, to prepare a chitosan solution with a concentration of 5-8% for standby use;

[0019] Step S5: Select porous silica as a carrier, mix lavender essential oil and porous silica in a ratio of 1:3, put into an ultrasonic oscillator, and perform ultrasonic treatment at 30-40° C. for 20-30 minutes to uniformly load the lavender essential oil on the porous silica;

[0020] Step S6: Select cyclodextrin as a carrier, mix tea polyphenols and cyclodextrin in a ratio of 1:2, and stir at 50-60° C. for 30-45 minutes to uniformly load the tea polyphenols on the cyclodextrin;

[0021] Step S7: adding the dried polylactic acid, starch-based polymer, plant short fibers, bamboo fibers, nano-calcium carbonate and biopolymer water-absorbing resin filler into a high-speed mixer according to the formula ratio, and mixing the mixture at a speed of 800-1100 rpm for 15-20 minutes at 50-55° C. to obtain a matrix A;

[0022] Step S8: adding lubricant, antioxidant and masterbatch to the matrix A in step S7, and continuing to mix at the same temperature and speed for 10-15 minutes, adding the carrier loaded with lavender essential oil and tea polyphenols into the mixer, and controlling the mixing system to mix at 800-1000 rpm for 15-20 minutes at 40-50°C;

[0023] Step S9: Based on step S8, polyvinyl alcohol solution and chitosan solution are continuously added, and the mixing system controls the device to stir at a speed of 500-800 rpm for 20-30 minutes at 40-50° C. to obtain a matrix B;

[0024] Step S10: After the base B in step S9 is put into a twin-screw extruder for extrusion molding, it is put into a biaxial stretching machine for stretching treatment, and the stretched bottom film is cooled and solidified to obtain a fully biodegradable diaper breathable bottom film.

[0025] Preferably, the drying process in step S1 is carried out in an environment with a relative humidity lower than 30%.

[0026] Preferably, the biopolymer water-absorbing resin filler in step S7 includes the following preparation steps:

[0027] Step k1: Add starch grafted acrylic acid into a reactor, add one-fourth volume of deionized water, stir evenly to make the concentration of starch grafted acrylic acid 20%-30%, heat to 80-90°C while stirring, and keep for 30-45 minutes to fully gelatinize the starch grafted acrylic acid; place the polylactic acid-polyethylene glycol copolymer and chitosan in a hot air circulation oven at 50-60°C for 4-6 hours to ensure that the moisture content is less than 0.5%;

[0028] Step k2: Add the gelatinized starch grafted acrylic acid into a reactor, add deionized water to make the total system concentration 15%-25%, stir evenly, heat to 65°C, add 1%-2% initiator based on the mass of starch grafted acrylic acid, stir at 300-400 rpm for 20-30 minutes to fully initiate the reaction;

[0029] Step k3: dropwise adding acrylic acid monomer, the mass ratio of acrylic acid to starch grafted acrylic acid is 4:1-5:1, the dropping speed is controlled to 5-10 ml per minute, the dropping time is 1-1.5 hours, after reacting for 2-3 hours, continue to add polylactic acid-polyethylene glycol copolymer and chitosan, and continue to react for 1-2 hours;

[0030] Step k4: After the reaction is completed, the product is cooled to room temperature, washed with a washing solution, filtered through a filter, and washed 3-4 times, each time using a solvent 3-5 times the volume of the product;

[0031] Step k5: placing the washed product into a centrifuge for centrifugal separation at a speed of 3000-4000 rpm for 10-15 minutes;

[0032] Step k6: Place the centrifuged product in a drying oven and dry it at 50-60° C. to a constant weight to obtain a biopolymer water-absorbing resin filler.

[0033] Preferably, in step k3, the mass ratio of the polylactic acid-polyethylene glycol copolymer to the starch grafted acrylic acid is 1:3-1:4, and the mass ratio of chitosan to the starch grafted acrylic acid is 1:5-1:6.

[0034] Preferably, the washing solution in step k4 is any one of ethanol or acetone, and the washing solution is preferably an ethanol solution.

[0035] Preferably, the control method of the blending system in step S7 specifically comprises the following steps:

[0036] Step 1: Install a temperature sensor and intelligent temperature control system in the mixer. The temperature sensor can accurately monitor the temperature changes at every location in the mixer in real time.

[0037] The intelligent temperature control system has powerful data analysis and automatic adjustment capabilities. When it detects that the temperature deviates from the set range, it can quickly and accurately adjust the heating or cooling power;

[0038] Step 2: Install a frequency converter on the rotating shaft of the mixer, which can flexibly adjust the speed of the stirring motor according to changes in the mixing process;

[0039] Step 3: Introduce advanced online monitoring technology and install viscosity monitoring equipment, which can monitor the viscosity changes of materials in real time and accurately;

[0040] Step 4: The mixer temperature range is strictly set to 50-55°C. Through a large number of experiments and data analysis, it is determined that within this temperature range, the material can maintain optimal fluidity and mixing performance;

[0041] Step 5: Set the viscosity threshold and determine the optimal viscosity range through precise experiments and data analysis according to different mixing stages and material combinations;

[0042] Step 6: According to steps 1 to 5, the preparation system is used to perform real-time regulation to complete the preparation of the matrix A.

[0043] The present invention provides a fully biodegradable breathable bottom film for diapers, which has the following beneficial effects:

[0044] 1. Good environmental protection: starch-based polymers enhance biodegradability and flexibility, bamboo fibers improve water absorption, natural antibacterial properties and accelerate degradation, photosensitizers accelerate the degradation rate of materials under light, and the use of biodegradable materials reduces pollution to the environment and meets the requirements of sustainable development.

[0045] 2. Good breathability: Plant short fibers increase softness and breathability. By adding a variety of ingredients, a microporous structure is formed, which improves the breathability of the base film, allowing the baby's skin to breathe and reducing the feeling of stuffiness and humidity.

[0046] 3. Strong water absorption performance: Biopolymer water-absorbent resin filler can absorb a large amount of water. At the same time, added ingredients such as bamboo fiber also have certain water absorption, which improves the water absorption performance of the base film and keeps the baby's skin dry.

[0047] 4. Good antibacterial performance: Polyvinyl alcohol enhances the antibacterial performance and stability of the material, tea polyphenols have antioxidant and antibacterial effects, lavender essential oil is a natural antibacterial agent, giving the base film a fresh smell, chitosan is a natural antibacterial agent, which improves the biocompatibility of the base film, and a variety of antibacterial ingredients are added to effectively inhibit the growth of bacteria and protect the baby's skin health.

[0048] 5. Simple preparation method: The preparation method of this scheme is relatively simple, using common equipment and processes, and is easy to realize industrial production.

[0049] 6. Stable performance: Polylactic acid (PLA) provides the basic structure and strength of the base film. By optimizing the formula and preparation process, the performance of the base film is stable and can meet the use requirements of diapers.

[0050] 7. Low cost: The use of some low-cost materials, such as starch-based polymers, plant short fibers, etc., reduces the cost of the base film and improves the competitiveness of the product. DETAILED DESCRIPTION

[0051] The following specific embodiments further describe the present invention in detail. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0052] Embodiment 1, a fully biodegradable breathable bottom film of a diaper, comprising the following components by weight: 45 parts by weight of polylactic acid, 35 parts by weight of starch-based polymer, 10 parts by weight of plant staple fibers, 8 parts by weight of bamboo fibers, 2 parts by weight of photosensitizer, 5 parts by weight of polyvinyl alcohol, 1 part by weight of lavender essential oil, 1 part by weight of tea polyphenols, 2 parts by weight of chitosan, 0.6 parts by weight of lubricant, 0.2 parts by weight of antioxidant, 2 parts by weight of nano-calcium carbonate, 0.4 parts by weight of masterbatch, and 4 parts by weight of biopolymer water-absorbing resin filler.

[0053] The plant short fibers are composed of hemp fibers, kapok fibers and coconut shell fibers, and the composition ratio of hemp fibers, kapok fibers and coconut shell fibers is 1:1:2;

[0054] The photosensitizer is phthalocyanine dye;

[0055] The antioxidant is dilauryl thiodipropionate;

[0056] The lubricant is glyceryl stearate;

[0057] The starch-based polymer is starch grafted with polyacrylic acid.

[0058] The biopolymer water-absorbing resin filler is composed of the following components by weight: 60 parts by weight of starch-grafted acrylic acid, 30 parts by weight of polylactic acid-polyethylene glycol copolymer, 10 parts by weight of chitosan, 0.5 parts by weight of initiator, 0.3 parts by weight of crosslinking agent and 0.2 parts by weight of surfactant.

[0059] The initiator is potassium persulfate;

[0060] The cross-linking agent is polyethylene glycol diacrylate;

[0061] The surfactant was Tween-80.

[0062] Example 2, a fully biodegradable breathable bottom film for diapers, comprising the following components by weight: 50 parts by weight of polylactic acid, 40 parts by weight of starch-based polymer, 11 parts by weight of plant staple fibers, 9 parts by weight of bamboo fibers, 3 parts by weight of photosensitizer, 7.5 parts by weight of polyvinyl alcohol, 2 parts by weight of lavender essential oil, 1.5 parts by weight of tea polyphenols, 3.5 parts by weight of chitosan, 0.8 parts by weight of lubricant, 0.35 parts by weight of antioxidant, 3 parts by weight of nano-calcium carbonate, 0.5 parts by weight of masterbatch, and 5.5 parts by weight of biopolymer water-absorbing resin filler.

[0063] The plant short fibers are composed of hemp fibers, kapok fibers and coconut shell fibers, and the composition ratio of hemp fibers, kapok fibers and coconut shell fibers is 1:1:2;

[0064] The photosensitizer is phthalocyanine dye;

[0065] The antioxidant is dilauryl thiodipropionate;

[0066] The lubricant is glyceryl stearate;

[0067] The starch-based polymer is starch grafted with polyacrylic acid.

[0068] The biopolymer water-absorbing resin filler is composed of the following components by weight: 65 parts by weight of starch-grafted acrylic acid, 35 parts by weight of polylactic acid-polyethylene glycol copolymer, 12.5 parts by weight of chitosan, 0.65 parts by weight of initiator, 0.4 parts by weight of crosslinking agent and 0.3 parts by weight of surfactant.

[0069] The initiator is potassium persulfate;

[0070] The cross-linking agent is polyethylene glycol diacrylate;

[0071] The surfactant was Tween-80.

[0072] Example 3, a fully biodegradable breathable bottom film for diapers, comprising the following components by weight: 55 parts by weight of polylactic acid, 45 parts by weight of starch-based polymer, 12 parts by weight of plant staple fibers, 10 parts by weight of bamboo fibers, 4 parts by weight of photosensitizer, 10 parts by weight of polyvinyl alcohol, 3 parts by weight of lavender essential oil, 2 parts by weight of tea polyphenols, 5 parts by weight of chitosan, 1 part by weight of lubricant, 0.5 parts by weight of antioxidant, 4 parts by weight of nano-calcium carbonate, 0.6 parts by weight of masterbatch, and 7 parts by weight of biopolymer water-absorbing resin filler.

[0073] The plant short fibers are composed of hemp fibers, kapok fibers and coconut shell fibers, and the composition ratio of hemp fibers, kapok fibers and coconut shell fibers is 1:1:2;

[0074] The photosensitizer is phthalocyanine dye;

[0075] The antioxidant is dilauryl thiodipropionate;

[0076] The lubricant is glyceryl stearate;

[0077] The starch-based polymer is starch grafted with polyacrylic acid.

[0078] The biopolymer water-absorbing resin filler is composed of the following components by weight: 70 parts by weight of starch-grafted acrylic acid, 40 parts by weight of polylactic acid-polyethylene glycol copolymer, 15 parts by weight of chitosan, 0.8 parts by weight of initiator, 0.5 parts by weight of crosslinking agent and 0.4 parts by weight of surfactant.

[0079] The initiator is potassium persulfate;

[0080] The cross-linking agent is polyethylene glycol diacrylate;

[0081] The surfactant was Tween-80.

[0082] Example 4, based on the above-mentioned examples 1, 2 and 3, a method for preparing a fully biodegradable breathable bottom film for diapers comprises the following preparation steps:

[0083] Step S1: placing polylactic acid, starch-based polymer, plant staple fiber, and bamboo fiber in a hot air circulation oven at 65° C. and drying for 5 hours, and taking them out after the moisture content is less than 0.5%;

[0084] Step S2: adding nano calcium carbonate into a high-speed stirrer, and simultaneously adding silane coupling agent KH-550, wherein the amount of silane coupling agent KH-550 is 2% of the nano calcium carbonate, and stirring at 45° C. for 40 minutes;

[0085] Step S3: adding polyvinyl alcohol to deionized water, stirring at 85° C. with a magnetic stirrer until the polyvinyl alcohol is completely dissolved, to prepare a polyvinyl alcohol solution with a concentration of 12.5% ​​for later use;

[0086] Step S4: adding chitosan to a dilute acetic acid solution with a pH value of 4.5, stirring with a magnetic stirrer at room temperature until the solution is completely dissolved, to prepare a chitosan solution with a concentration of 5-8% for later use;

[0087] Step S5: selecting porous silica as a carrier, mixing lavender essential oil and porous silica in a ratio of 1:3, placing the mixture in an ultrasonic oscillator, and ultrasonically treating the mixture at 35° C. for 25 minutes to uniformly load the lavender essential oil on the porous silica;

[0088] Step S6: selecting cyclodextrin as a carrier, mixing tea polyphenols and cyclodextrin in a ratio of 1:2, and stirring at 55° C. for 38 minutes to uniformly load the tea polyphenols on the cyclodextrin;

[0089] Step S7: adding the dried polylactic acid, starch-based polymer, plant short fibers, bamboo fibers, nano-calcium carbonate and biopolymer water-absorbing resin filler into a high-speed mixer according to the formula ratio, and controlling the mixing system to mix at a speed of 1000-1100 rpm for 15-20 minutes at 50-55° C. to obtain a matrix A;

[0090] Step S8: adding lubricant, antioxidant and masterbatch to the matrix A in step S7, and continuing to mix at the same temperature and speed for 13 minutes, adding the carrier loaded with lavender essential oil and tea polyphenols into the mixer, and mixing the mixture at 45° C. and 900 rpm for 18 minutes under the control of the mixing system;

[0091] Step S9: Based on step S8, polyvinyl alcohol solution and chitosan solution are continuously added, and the mixing system controls the device to stir at 45° C. and 650 rpm for 25 minutes to obtain a matrix B;

[0092] Step S10: After the base B in step S9 is put into a twin-screw extruder for extrusion molding, it is put into a biaxial stretching machine for stretching treatment, and the stretched bottom film is cooled and solidified to obtain a fully biodegradable diaper breathable bottom film.

[0093] The drying process in step S1 is performed in an environment with a relative humidity lower than 30%.

[0094] The biopolymer water-absorbing resin filler in step S7 includes the following preparation steps:

[0095] Step k1: Add starch grafted acrylic acid into a reactor, add one-fourth volume of deionized water, stir evenly to make the concentration of starch grafted acrylic acid 25%, heat to 85°C while stirring, and keep for 38 minutes to fully gelatinize the starch grafted acrylic acid; place the polylactic acid-polyethylene glycol copolymer and chitosan in a hot air circulation oven at 55°C for 5 hours to ensure that the moisture content is less than 0.5%;

[0096] Step k2: Add the gelatinized starch grafted acrylic acid into a reactor, add deionized water to make the total system concentration 20%, stir evenly, heat to 65°C, add 1.5% initiator based on the mass of starch grafted acrylic acid, and stir at 350 rpm for 25 minutes to fully initiate the reaction;

[0097] Step k3: dropwise addition of acrylic acid monomer, with the mass ratio of acrylic acid to starch-grafted acrylic acid being 4.5:1, and the dropping speed being controlled to be 7.5 ml per minute for 1.25 hours. After reacting for 2.5 hours, polylactic acid-polyethylene glycol copolymer and chitosan are continuously added, and the reaction is continued for 1.5 hours;

[0098] Step k4: After the reaction is completed, the product is cooled to room temperature, washed with a washing solution, filtered through a filter, and washed 4 times, each time using a solvent 4 times the volume of the product;

[0099] Step k5: placing the washed product into a centrifuge for centrifugal separation at a speed of 3500 rpm for 12.5 minutes;

[0100] Step k6: Place the centrifuged product in a drying oven and dry it at 55° C. to a constant weight to obtain a biopolymer water-absorbing resin filler.

[0101] The mass ratio of the polylactic acid-polyethylene glycol copolymer to the starch grafted acrylic acid in step k3 is 1:3.5, and the mass ratio of chitosan to the starch grafted acrylic acid is 1:5.5.

[0102] The washing solution in step k4 is an ethanol solution.

[0103] The control method of the deployment system in step S7 specifically comprises the following steps:

[0104] Step 1: Install a temperature sensor and intelligent temperature control system in the mixer. The temperature sensor can accurately monitor the temperature changes at every location in the mixer in real time.

[0105] The intelligent temperature control system has powerful data analysis and automatic adjustment capabilities. When it detects that the temperature deviates from the set range, it can quickly and accurately adjust the heating or cooling power;

[0106] Step 2: Install a frequency converter on the rotating shaft of the mixer, which can flexibly adjust the speed of the stirring motor according to changes in the mixing process;

[0107] Step 3: Introduce advanced online monitoring technology and install viscosity monitoring equipment, which can monitor the viscosity changes of materials in real time and accurately;

[0108] Step 4: The mixer temperature range is strictly set to 50-55°C. Through a large number of experiments and data analysis, it is determined that within this temperature range, the material can maintain optimal fluidity and mixing performance;

[0109] Step 5: Set the viscosity threshold and determine the optimal viscosity range through precise experiments and data analysis according to different mixing stages and material combinations;

[0110] Step 6: According to steps 1 to 5, the preparation system is used to perform real-time regulation to complete the preparation of the matrix A.

[0111] The control method of the deployment system is divided into the following stages:

[0112] Initial efficient fusion stage (first 15% of time):

[0113] Precise temperature control: Keep the temperature stable at around 55°C. Using advanced temperature control systems to ensure minimal temperature fluctuations, this higher temperature can greatly promote the flow and initial mixing of materials. Especially for major ingredients such as polylactic acid and starch-based polymers, it can enable them to enter the mixing state at a faster speed, laying a solid foundation for the subsequent mixing process.

[0114] Optimize stirring speed control: Stir at a lower speed of 800 rpm. Through the precise control of the high-performance inverter, the stirring speed is ensured to be stable at this lower level, effectively preventing material splashing and loss. Especially for fine particle materials such as nano calcium carbonate, it can significantly reduce their flying and loss during the stirring process, and improve the utilization rate of materials.

[0115] Smooth transition phase (5% of the time):

[0116] Fine temperature control: gradually reduce the temperature to 53°C. During this transition phase, the intelligent temperature control system adjusts the temperature in a gradual manner to ensure a smooth temperature change, fully preparing for the subsequent stable mixing phase.

[0117] Intelligent stirring speed control: The stirring speed is gradually increased under the control of a high-performance inverter. Through precise speed adjustment, good conditions are created for entering the intermediate mixing stage.

[0118] Core stabilization mixing phase (60% of the time):

[0119] Stable temperature control: The temperature is maintained at 53°C. The intelligent temperature control system continuously monitors the temperature to ensure that the temperature is always stable within the optimal range during this critical stage. This temperature can not only maintain the stability of the mixture, but also prevent the material from changing or degrading due to excessive temperature. For ingredients such as plant short fibers and bamboo fibers, they can better blend with other materials at this temperature to achieve full interaction between the ingredients.

[0120] Efficient stirring speed control: The stirring speed is gradually increased to 1000-1100 rpm under the precise control of the high-performance inverter. At this stage, the interaction between the materials gradually increases, and the higher stirring speed can promote the full mixing of the components. For key ingredients such as biopolymer absorbent resin fillers, they can be better dispersed in the matrix at this speed to ensure the performance of the final product.

[0121] Transition phase again:

[0122] Precise temperature control: Lower the temperature again to 52°C. The intelligent temperature control system controls the temperature drop in a precise manner, preparing for the final mixing and adjustment phase.

[0123] Stable stirring speed control: The stirring speed is gradually stabilized under the control of a high-performance inverter, creating a stable mixing environment for the final stage.

[0124] Final fine-tuning phase (last 20% of time):

[0125] Strict temperature control: Lower the temperature to 52°C. At this point, the intelligent temperature control system continuously monitors the temperature to ensure that the materials have been basically mixed evenly. Lowering the temperature can prevent the materials from overheating and degradation, ensuring that the quality of the final product meets the highest standards.

[0126] Optimized stirring speed control: The stirring speed is stabilized at 1100 rpm. Through the precise control of the high-performance inverter, the stirring speed is ensured to be stable at this level, mainly to ensure the uniformity of mixing and make the final fine adjustment and optimization of the entire mixing system.

[0127]

[0128] In summary, from Example 1 to Example 3, the air permeability, water absorption and stretchability of the base film show a trend of gradual improvement.

[0129] In terms of air permeability, Example 3 has the highest content of components that help form a microporous structure, such as plant short fibers and bamboo fibers, and can provide more channels for air circulation, thus having the best air permeability, which can effectively reduce the stuffiness and humidity of the baby's skin and improve comfort.

[0130] Regarding water absorption, Example 3 has the highest content of key water-absorbing components such as biopolymer water-absorbing resin filler, which enables it to have the strongest water absorption capacity, quickly absorb and store a large amount of water, and keep the inside of the diaper dry even when the baby urinates a large amount, reducing the risk of skin infection.

[0131] In terms of stretchability, the polylactic acid and reinforced fiber content of Example 3 have obvious advantages, so that the base film has the highest tensile strength and elongation at break, can better adapt to various stretching conditions caused by baby's activities, and ensure the integrity and functionality of the base film during use.

[0132] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A fully biodegradable breathable bottom film for diapers, characterized in that: The invention comprises the following components by weight: 45-55 parts by weight of polylactic acid, 35-45 parts by weight of starch-based polymer, 10-12 parts by weight of plant short fibers, 8-10 parts by weight of bamboo fibers, 2-4 parts by weight of photosensitizer, 5-10 parts by weight of polyvinyl alcohol, 1-3 parts by weight of lavender essential oil loaded on porous silica, 1-2 parts by weight of tea polyphenol loaded on cyclodextrin, 2-5 parts by weight of chitosan, 0.6-1 parts by weight of lubricant, 0.2-0.5 parts by weight of antioxidant, 2-4 parts by weight of nano calcium carbonate, 0.4-0.6 parts by weight of masterbatch, and 4-7 parts by weight of biopolymer water-absorbing resin filler; The biopolymer water-absorbing resin filler is composed of the following weight components: 60-70 weight parts of starch grafted acrylic acid, 30-40 weight parts of polylactic acid-polyethylene glycol copolymer, 10-15 weight parts of chitosan, 0.5-0.8 weight parts of initiator, 0.3-0.5 weight parts of cross-linking agent, and 0.2-0.4 weight parts of surfactant; The plant short fibers consist of hemp fibers, kapok fibers and coconut shell fibers.

2. A fully biodegradable breathable bottom film for diapers according to claim 1, characterized in that: The starch-based polymer is any one of starch grafted polyacrylic acid and starch grafted polyvinyl alcohol.

3. A fully biodegradable breathable bottom film for diapers according to claim 2, characterized in that: The initiator is any one of potassium persulfate, ammonium persulfate, azobisisobutyronitrile and benzoyl peroxide; The cross-linking agent is any one of polyethylene glycol diacrylate, trimethylolpropane triacrylate and divinylbenzene; The surfactant is any one of sodium dodecylbenzene sulfonate, Tween-80 and Span-80.

4. The fully biodegradable breathable bottom film of diapers according to claim 1, characterized in that: The method for preparing the fully biodegradable breathable bottom film of diapers comprises the following preparation steps: Step S1: placing polylactic acid, starch-based polymer, plant staple fiber, and bamboo fiber in a hot air circulation oven at 60-70° C. and drying for 4-6 hours, and taking them out after the moisture content is less than 0.5%; Step S2: Add nano calcium carbonate into a high-speed mixer, and add silane coupling agent KH-550 at the same time, and stir at 40-50° C. for 30-45 minutes; Step S3: adding polyvinyl alcohol to deionized water, stirring with a magnetic stirrer at 80-90° C. until the polyvinyl alcohol is completely dissolved, to prepare a polyvinyl alcohol solution with a concentration of 10-15% for standby use; Step S4: adding chitosan to a dilute acetic acid solution with a pH value of 4-5, stirring with a magnetic stirrer at room temperature until the solution is completely dissolved, to prepare a chitosan solution with a concentration of 5-8% for later use; Step S5: Select porous silica as a carrier, mix lavender essential oil and porous silica in a ratio of 1:3, put into an ultrasonic oscillator, and perform ultrasonic treatment at 30-40° C. for 20-30 minutes to uniformly load the lavender essential oil on the porous silica; Step S6: Select cyclodextrin as a carrier, mix tea polyphenols and cyclodextrin in a ratio of 1:2, and stir at 50-60° C. for 30-45 minutes to uniformly load the tea polyphenols on the cyclodextrin; Step S7: adding the dried polylactic acid, starch-based polymer, plant short fibers, bamboo fibers, nano-calcium carbonate and biopolymer water-absorbing resin filler into a high-speed mixer according to the formula ratio, and mixing the mixture at a speed of 800-1100 rpm for 15-20 minutes at 50-55° C. to obtain a matrix A; Step S8: adding lubricant, antioxidant and masterbatch to the matrix A in step S7, and continuing to mix at the same temperature and speed for 10-15 minutes, adding the carrier loaded with lavender essential oil and tea polyphenols into the mixer, and controlling the mixing system to mix at 800-1000 rpm for 15-20 minutes at 40-50°C; Step S9: Based on step S8, polyvinyl alcohol solution and chitosan solution are continuously added, and the mixing system controls the device to stir at a speed of 500-800 rpm for 20-30 minutes at 40-50° C. to obtain a matrix B; Step S10: After the base B in step S9 is put into a twin-screw extruder for extrusion molding, it is put into a biaxial stretching machine for stretching treatment, and the stretched bottom film is cooled and solidified to obtain a fully biodegradable diaper breathable bottom film.

5. A fully biodegradable breathable bottom film for diapers according to claim 4, characterized in that: The drying process in step S1 is performed in an environment with a relative humidity lower than 30%.

6. A fully biodegradable breathable bottom film for diapers according to claim 4, characterized in that: The biopolymer water-absorbing resin filler in step S7 includes the following preparation steps: Step k1: Add the gelatinized starch grafted with acrylic acid into a reactor, add one-fourth volume of deionized water, stir evenly to make the starch concentration 20%-30%, heat to 80-90°C while stirring, and keep for 30-45 minutes to fully gelatinize the starch; place the polylactic acid-polyethylene glycol copolymer and chitosan in a hot air circulation oven at 50-60°C for 4-6 hours to ensure that the moisture content is less than 0.5%; Step k2: Add the gelatinized starch to a reactor, add deionized water to make the total system concentration 15%-25%, stir evenly, heat to 65°C, add 1%-2% initiator of the mass of starch grafted acrylic acid, stir at 300-400 rpm for 20-30 minutes to fully initiate the reaction; Step k3: adding acrylic acid monomer dropwise, with the mass ratio of acrylic acid to starch being 4:1-5:1, controlling the dropping speed to be 5-10 ml per minute, and the dropping time to be 1-1.5 hours. After reacting for 2-3 hours, continue to add polylactic acid-polyethylene glycol copolymer and chitosan, and continue to react for 1-2 hours; Step k4: After the reaction is completed, the product is cooled to room temperature, washed with a washing solution, filtered through a filter, and washed 3-4 times, each time using a solvent 3-5 times the volume of the product; Step k5: placing the washed product into a centrifuge for centrifugal separation at a speed of 3000-4000 rpm for 10-15 minutes; Step k6: Place the centrifuged product in a drying oven and dry it at 50-60° C. to a constant weight to obtain a biopolymer water-absorbing resin filler.

7. A fully biodegradable breathable bottom film for diapers according to claim 6, characterized in that: The mass ratio of the polylactic acid-polyethylene glycol copolymer to starch in step k3 is 1:3-1:4, and the mass ratio of chitosan to starch is 1:5-1:

6.

8. The fully biodegradable breathable bottom film of diapers according to claim 6, characterized in that: The washing solution in step k4 is any one of ethanol or acetone.

Citation Information

Patent Citations

  • Environment-friendly non-toxic biodegradable garbage bag and preparation method thereof

    CN118852774A